Authentication of Wax Apple (Syzygium samarangense (Blume) Merr. & L.M Perry) Delima and Citra Cultivars by Morphological and Molecular Approach - Mukaromah, Arnia Sari; Ulfah, Malia; Rachmah, Annisa Nur; Arfan, Muhammad Ramdhani; Kusumarini, Niken; Febriana, Asri (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2023)
Wax apple Delima and Citra Cultivars are two superior non-climacteric tropical fruit commodities from Demak Regency which have similar morphological characters but have different fruit characteristics. Identification wax apple cultivars from Demak regency using DNA barcoding approach has not been researched yet. The aims of this research are to analyze the morphological similarities of wax apple between Delima and Citra cultivars and to identify genetic variations of wax apple Delima and Citra using trnL-trnF intergenic spacer for molecularly authentication. The results shown that there were no differences in the environmental parameters of the wax apple two cultivated area in Demak Regency. According to the morphological approach, the Delima and Citra cultivars in Demak Regency were grouped separately into Delima and Citra clusters with a similarity index of 61.5% (Citra cultivars) and 60.5% (Delima cultivars) and separated based on the origin of their cultivation area. Genetic variations between wax apple Delima and Citra in Demak Regency consisted of deletions (9delA & 17delA) and conserved P6 loop in all compared cultivars. The possibility of heteroplasmy R (A,G) found at 73 nucleotide number in Delima Betokan cultivar and Citra cultivars (Betokan and Jungpasir). Meanwhile, Delima Jungpasir cultivar is K (G,T). There were P8 stem-loops with different lengths between Delima cultivars (Betokan and Jungpasir) and the same length in Citra cultivars (Betokan and Jungpasir). Therefore, the trnL-trnF intergenic spacer has not been thoroughly used in wax apple Delima and Citra authentication due to the presence of a secondary structure which causes the loss of the electropherogram signal so that the nucleotide sequence cannot be read.